Western Gate in Leptis Magna (Porta Oea) as Antoninus Pius Triumphal Arch - Mosiejczyk, Jakub (Acta Archaeologica Lodziensia, 2020)
The aim of the presented study is to consider the remains of the Western Gate in Leptis Magna as a relic of the triumphal arch in the urban and social context of the city. The monument is relatively unknown and functions among researchers mainly as the monument of late ancient fortifications. The history and current state of the research on the architecture and decoration of this object is described in the light of studies and deliberations. Presented here is an iconographic analysis of the few details discovered near the monument, including a figural representation featuring a Medusa medallion. Conclusions on the stylistics of the arch decorations point to the work of craftsmen from Asia Minor. The importance of the phenomenon, which in the middle of the 2nd century begins the process of transformation of the city with the use of a newly imported raw material – marble, was emphasized. These processes resulted in the formation of the local North African architectural style in public buildings.